Up All Night Out of Love for the Prophet: Devotion, Sanctity, and Ritual Innovation in the Ottoman Arab Lands, 1500–1620. (5th June 2019) - Allen, Jonathan Parkes
Abstract: Devotion to the Prophet Muḥammad was a major feature of late medieval and early modern Islamic religious life across much of the Islamic world. The history of this devotion remains understudied in relation to its importance and pervasiveness. This study takes as its locus of analysis a particular instance of early modern devotion: a weekly, public all-night session of ṣalawāt upon the Prophet that would become known as the maḥyā . Developed by the peasant-turned-shaykh Nūr al-Dīn al-Shūnī in late Mamluk Egypt, performance of the maḥyā would spread over the following century throughout the Arab Ottoman world, undergoing changes, provoking controversy, and becoming embedded in the sacred spaces and ritual life of one city after another. I approach the history of the maḥyā as a discrete and legible instance of ritual change in an Islamic context, exploring this instance of communal devotion to the Prophet through such lenses as ritual studies and the spatial turn, examining the intersection of this devotional ritual with practices of subjectivity, the use and contestation of ritual space, and the meaning, regulation, and experience of the night.